Research and digital skills in postgraduate students: a bibliometric analysis (Revista Electrónica Calidad en la Educación Superior, 2024)
This paper aims to investigate, from a theoretical point of view, the possible relationship between research and digital competences necessary or required in graduate students to develop efficiently during their educational training, since this academic degree has a high research component and there are more and more technological tools that can be used to carry out the tasks required in the research process. It focuses on qualitative research and the data collection is based on a documentary analysis; the bibliographic manager Mendeley was used for the analysis process and the VOSviewer software version 1.6.7 was implemented for the inquiry of the structure and subject matter. The bibliographic review yielded 51 documents published in indexed journals, from which a series of keywords related to the study are considered, as well as several clusters that establish important relationships between them, from which it can be determined that research competencies are related to digital competencies since many of the activities proposed in the design of research are supported by the use of Information and Communication Technologies (ICT). It is concluded that by considering research as a set of actions carried out to acquire new knowledge and skills that allow the implementation of tools that range from the use of databases to the use of specialized statistical programs and reliable digital media to disseminate results, which require that the student body master’s through digital skills.
Keywords: research skills; digital skills; students; distance university education